Adobe Flash CS6 to Develop Mathematics Learning Media for Plane Geometry - Farida Farida; Farida Hanum; Abdul Rahim (Didaktik Matematika, 2021)
Student can master the materials by doing the problems repeatedly. A media enables students work on varied random problems is necessary. This study aimed to provide valid, practical, and effective learning media. This research was a development research, involving 64 junior high school students in Yogyakarta. The instruments used in this study were expert validation sheets, questionnaires, and tests. The data was analyzed using a quantitative descriptive statistical analysis. Descriptive statistics was used to analyze data from students' tests. Meanwhile, descriptive qualitative was to describe the data of suggestions and comments from the validators for improvement. The results of expert validation for the media aspect achieved a very feasible category, while the material aspect also reached a very feasible category. Besides, the questionnaire results on student responses to learning media were also classified as a very practical category. The students' scores met the minimum criteria of mastery learning, meaning that the learning media achieved a very effective criterion. The results of this study imply that learning media can be used as an alternative in improving student learning outcomes.